The Role Of Teacher and Student Interpersonal Communication in Developing Awareness of Gadget Use: A Case Study at State Elementary School 2 Perumnas Way Kandis - Cahyani, Hani Regita; Hernawan, Wawan; Poyo, M. Denu (Interaction Communication Studies Journal, 2025)
This study aims to determine and analyze the role of interpersonal communication between teachers and students in fostering awareness of gadget use at SD Negeri 2 Perumnas Way Kandis. Interpersonal communication is considered a key factor in shaping student behavior, particularly regarding the wise use of technology in the school environment. Teachers, as key figures in the school environment, have a significant responsibility in conveying values ​​and information regarding the positive and negative impacts of gadget use. The method used was a qualitative approach with a case study design. Data collection techniques included observation, in-depth interviews, and documentation. The informants in this study consisted of 15 individuals, including teachers, sixth-grade students, and parents, selected using purposive sampling and snowball sampling techniques. Data validity was tested through source triangulation to ensure the accuracy and reliability of the information. The results showed that teachers' interpersonal communication, which encompasses openness, empathy, support, equality, and a positive attitude, proved effective in raising students' awareness regarding gadget use. Teachers who are able to create two-way communication, provide open dialogue, and demonstrate empathy, are able to foster students' understanding and wise attitudes regarding gadget use. Furthermore, collaboration between teachers and parents also strengthens the implementation of gadget use rules both at school and at home. Consistent and educational communication makes students more aware of the time, content, and purpose of gadget use. This research confirms that good interpersonal communication between teachers and students is a crucial foundation for character education and digital literacy from an early age.